Heteroatom-doped highly porous carbon from human urine - Chaudhari, Nitin Kaduba (Nature Publishing Group, 2014)
Human urine, otherwise potentially polluting waste, is an universal unused resource in organic form disposed by the human body. We present for the first time “proof of concept” of a convenient, perhaps economically beneficial, and innovative template-free route to synthesize highly porous carbon containing heteroatoms such as N, S, Si, and P from human urine waste as a single precursor for carbon and multiple heteroatoms. High porosity is created through removal of inherently-present salt particles in as-prepared “Urine Carbon” (URC), and multiple heteroatoms are naturally doped into the carbon, making it unnecessary to employ troublesome expensive pore-generating templates as well as extra costly heteroatom-containing organic precursors. Additionally, isolation of rock salts is an extra bonus of present work. The technique is simple, but successful, offering naturally doped conductive hierarchical porous URC, which leads to superior electrocatalytic ORR activity comparable to state of the art Pt/C catalyst along with much improved durability and methanol tolerance, demonstrating that the URC can be a promising alternative to costly Pt-based electrocatalyst for ORR. The ORR activity can be addressed in terms of heteroatom doping, surface properties and electrical conductivity of the carbon framework.